2021
DOI: 10.1186/s13075-021-02650-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term clinical response in patients with non-radiographic axial spondyloarthritis receiving certolizumab pegol

Abstract: Background Identification of predictive clinical factors of long-term treatment response may contribute to improved management of non-radiographic axSpA (nr-axSpA) patients. This analysis aims to identify whether any baseline characteristics or Week 12 clinical outcomes in nr-axSpA patients with elevated C-reactive protein (CRP) and/or sacroiliitis on magnetic resonance imaging (MRI) enrolled in the C-axSpAnd study are predictive of achieving clinical response after 1 year of certolizumab pegol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…This result was unexpected as it was observed that patients with active inflammatory disease were more likely to benefit from anti-TNF. 25 Although >20% of the data for OSI were missing, the variable was forced into the multivariate model irrespective of its significance level or rate of missing data. In this study, the majority (>85%) of patients presented with OSI at treatment initiation, which might also impact the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was unexpected as it was observed that patients with active inflammatory disease were more likely to benefit from anti-TNF. 25 Although >20% of the data for OSI were missing, the variable was forced into the multivariate model irrespective of its significance level or rate of missing data. In this study, the majority (>85%) of patients presented with OSI at treatment initiation, which might also impact the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In various RCTs and RWE studies of axSpA patients, the factors reported to influence anti-TNF therapy efficacy and retention rate are smoking status, young age, gender, HLA-B27 positivity, radiographic status, OSI and rank of drug administration 24 25. This study aimed to evaluate whether OSI is associated with secukinumab retention and to determine if other predictive factors could be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following baseline factors that were considered potential response predictors for TNFi [12][13][14][15][16][17][18][19][20][21] were included in the univariate and multivariable analyses for P2 and P3: age (< 40 yrs vs ≥ 40 yrs), BMI (calculated as weight in kilograms divided by height in meters squared; < 25 vs ≥ 25), symptom duration (< 2 yrs vs ≥ 2 yrs), enthesitis (no enthesitis vs enthesitis), HLA-B27 status (negative vs positive), high-sensitivity CRP (hs-CRP; ≤ 3 mg/L vs > 3 mg/L), sacroiliitis on MRI at screening (negative vs positive), MRI SIJ SPARCC score (≤ 2 vs > 2), positive MRI plus hs-CRP > 3 mg/L (yes vs no), race (non-White vs White), sex, and weight (< 70 kg vs ≥ 70 kg).…”
Section: Methodsmentioning
confidence: 99%
“…Treatment recommendations from the ASAS/EULAR suggest that patients start with bDMARDs early in the disease process when they have active disease, despite the use (or intolerance/contraindication) of at least two NSAIDs, and have OSI, evidenced by elevated C-reactive protein (CRP) and/or sacroiliitis on magnetic resonance imaging (MRI) [23]. In the context of OSI, it has been shown that positive MRI is the strongest independent predictor of better response to CZP in patients with nr-axSpA [24]. Furthermore, licensed indications of all bDMARDs are restricted to patients with OSI whose presence is also required by most reimbursement policies.…”
Section: Introductionmentioning
confidence: 99%